Social and Psychological Effects of Radiological Terrorism. - Khripunov, Igor (NATO Science for Peace and Security Series: Human and Societal Dynamics, v. 29., 2007)
The threat of radiological terrorism has recently come to the attention of the international community, as it became clear that terrorist organizations are seeking nuclear and radiological material to manufacture and use improvised nuclear devices (IND) and 'dirty bombs', and/or commit acts of sabotage against nuclear power infrastructure.